2006
DOI: 10.1038/oby.2006.43
|View full text |Cite
|
Sign up to set email alerts
|

Visceral Fat Is an Independent Predictor of All‐cause Mortality in Men

Abstract: Dallas, TX, between 1995 and, with a mean mortality follow-up of 2.2 Ϯ 1.3 years. Abdominal fat was determined using contiguous CT images from the L3-L4 to L4-L5 intervertebral space. Liver fat was assessed using the CT-determined liver attenuation value, which is inversely related to liver fat. Logistic regression was used to determine the independent association between the fat depots and all-cause mortality. Results: During the study, there were 97 deaths. Visceral fat [odds ratio (OR) per SD: 1.83; 95% CI:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
440
1
6

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 539 publications
(463 citation statements)
references
References 37 publications
16
440
1
6
Order By: Relevance
“…Indeed, independent of subcutaneous fat, visceral fat is a strong predictor of dyslipidemia (20,21), glucose tolerance (22,23), insulin resistance (24) and systemic inflammation (25), as well as incidence of hypertension (26), CVD (7), type 2 diabetes (27) and all-cause mortality (28). These observations underscore the notion that both WC and visceral fat should be primary targets for strategies designed to reduce obesity and related CVD risk.…”
Section: Wc Visceral Obesity and Cardiometabolic Riskmentioning
confidence: 97%
“…Indeed, independent of subcutaneous fat, visceral fat is a strong predictor of dyslipidemia (20,21), glucose tolerance (22,23), insulin resistance (24) and systemic inflammation (25), as well as incidence of hypertension (26), CVD (7), type 2 diabetes (27) and all-cause mortality (28). These observations underscore the notion that both WC and visceral fat should be primary targets for strategies designed to reduce obesity and related CVD risk.…”
Section: Wc Visceral Obesity and Cardiometabolic Riskmentioning
confidence: 97%
“…Abdominal obesity seems to be a better predictor than overall obesity for the risk of CVD and type II diabetes, as well as being a strong predictor of morbidity and mortality in adults, independently of body mass index. 30 In population studies, waist circumference has shown to be an accurate measurement for intra-abdominal and subcutaneous fat, measured by magnetic resonance imaging, in children and adolescents. 31 Data from the Alimentació n y Valoració n del Estado Nutricional de los Adolescents [Food and Assessment of the Nutritional Status of Spanish Adolescents] (AVENA) study, a multicenter cross-sectional study carried out in 2859 Spanish adolescents, 32,33 show that both moderate to high levels of cardiorespiratory fitness are associated with lower abdominal adiposity ( Figure 2).…”
Section: Physical Fitness and Health Outcomesmentioning
confidence: 99%
“…Interestingly, although sensory vagotomy non-significantly reduced body weight, it also modestly, but significantly and selectively, reduced visceral abdominal fat by 18% compared with controls. This is an important finding given the aforementioned association of central obesity with several causes of morbidity and mortality and since small changes in the size of the visceral fat depot can exert sizeable influences on overall mortality risk [9]. Stearns et al [8] further suggested that sensory vagotomy could provide a valuable adjunct to bariatric surgery by enhancing its ability to reduce body fat, and in particular visceral fat.…”
Section: As Of the 2007-2008 National Health And Nutritionmentioning
confidence: 97%